Causality between school education and economic growth in Romania. - Dănăcică, Daniela-Emanuela (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2011)
This study investigates the causal relation between school education and economic growth in Romania, using annual time series data from 1985 to 2009. The econometric approach of this paper is based on the bivariate Vector Autoregression (VAR) model, Granger causality test and unit root test. The empirical results show evidence of unidirectional causality between school education and economic growth in Romania
Argumenta Oeconomica, 2011, Nr 1 (26), s. 57-72
Keywords: school education; economic growth; granger causality; cointegration; edukacja; wzrost gospodarczy; kointegracja